Pemodelan inversi gayaberat dengan panduan Euler deconvolution untuk struktur bawah permukaan di Lapangan Panas Bumi ”B24” - Brandan Tito Ramadhan; Agus Setyawan; Dwi P. Sasongko; Imam Baru Raharjo; R. M. Tofan Sastranegara (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Gravity data inversion requires a good initial mesh model to generate a good subsurface model. Ambiguities in gravity data can be reduced by Euler deconvolution’s point cluster result that show its position and depth. These point cluster can give an additional information to shape the initial mesh model for inversion. The purpose of the study was to determine the influence of Euler deconvolution to the inversion. Inversion was done by the steepest descent algorithm. Euler deconvolution method and inversion algorithm were tested on synthetic models and showed good results that Euler deconvolution able to construct actual density distribution. These methods were applied to the gravity data on the